"… to rely on first and foremost and always": Revisiting the role of introspection in William James's early psychological work. (February 2016) - Araujo, Saulo de Freitas; de Souza, Rayssa Maluf
In order to legitimate itself as a science, psychology has faced the ongoing problem of establishing its proper method of investigation. In this context, debates on introspection have emerged that have remained intense since the 18th century. However, contemporary debates and historical investigations on this topic have not done justice to the richness and diversity of positions, leading to oversimplifications and hasty generalizations, as if the terms "introspection" and "introspectionism" referred to one and same thing. The central goal of this article is to offer an analysis of William James's position on the introspective method within the intellectual context of his time, covering the period from his early writings until the publication, in 1890, of The Principles of Psychology . Our results indicate that James used two different types of introspection. We conclude by discussing divergences in the secondary literature and the implications of our study for historical and theoretical debates in psychology.